Leukemia‐associated Rho guanine‐nucleotide exchange factor is not critical for RhoA regulation, yet is important for platelet activation and thrombosis in mice. (20th October 2015) - Williams, C. M.; Harper, M. T.; Goggs, R.; Walsh, T. G.; Offermanns, S.; Poole, A. W.
Summary: Background: RhoA is an important regulator of platelet responses downstream of Gα13, yet we still know little about its regulation in platelets. Leukemia‐associated Rho guanine‐nucleotide exchange factor (GEF [LARG]), a RhoA GEF, is highly expressed in platelets and may constitute a major upstream activator of RhoA. To this end, it is important to determine the role of LARG in platelet function and thrombosis. Methods and results: Using a platelet‐specific gene knockout, we show that the absence of LARG results in a marked reduction in aggregation and dense‐granule secretion in response to the thromboxane mimetic U46619 and proteinase‐activated receptor 4–activating peptide, AYPGKF, but not to adenosine diphosphate. In a ferric chloride thrombosis model in vivo, this translated into a defect, under mild injury conditions. Importantly, agonist‐induced RhoA activation was not affected by the absence of LARG, although basal activity was reduced, suggesting that LARG may play a housekeeper role in regulating constitutive RhoA activity. Conclusions: LARG plays an important role in platelet function and thrombosis in vivo . However, although LARG may have a role in regulating the resting activation state of RhoA, its role in regulating platelet function may principally be through RhoA‐independent pathways, possibly through other Rho family members.